Institutional-Political Scenarios for Anthropocene Society. Issue 1 (January 2021) - Hoffman, Andrew J.; Jennings, P. Devereaux
Natural scientists have proposed that humankind has entered a new geologic epoch. Termed the "Anthropocene, " this new reality revolves around the central role of human activity in multiple Earth ecosystems. That challenge requires a rethinking of social science explanations of organization and environment relationships. In this article, we discuss the need to politicize institutional theory as a means understanding "Anthropocene Society, " and in turn what that resultant society means for the Anthropocene in the natural environment. We modify the constitutive elements of institutional orders and a set of main change mechanisms to explore three scenarios around which future Anthropocene Societies might be built—Collapsing Systems, Market Rules, and Cultural Re-Enlightenment. Simultaneously, we use observations from the Anthropocene to expose limitations in present institutional theory and propose extensions to remedy them. Overall, this article challenges organizational scholars to consider a new paradigm under which research in environmental sustainability and social sustainability takes place.